Responses of Wheat Genotypes to Salt Stress in Relation to Germination and Seedling Growth - Khatun, M.; Hafiz, M. H. R.; Hasan, M. A.; Hakim, M. A.; Siddiqui, M. N. (International Journal of Bio-resource and Stress Management, 2023)
To evaluate germination characters and seedling growth of wheat as screening criteria against salt stress, twenty wheat genotypes were tested at crop physiology and ecology Laboratory, Hajee Mohammad Danesh Science and Technology University (HSTU), Dinajpur during October to November 2010. Speed of germination as expressed by rate of germination, co-efficient of germination and germination vigor index of all wheat genotypes was delayed due to salinization compared to control but the degree of reduction in all the three parameters from control to 12 dS m-1 salinity level was not similar for all wheat genotypes. Shoot length and root length of 10 days old seedlings were found to be affected due to salinization and the increment in root to shoot length ratio at saline condition indicated shoot was more affected than root in saline condition. The magnitude of variation in all the four parameters from control to 12 dSm-1 salinity level was not similar for all wheat genotypes. Salt tolerance index (STI) based on seedling dry weight (10 days old) indicated a wide difference in salt tolerance among the wheat genotypes. Shatabdi, BAW 1135 and Bijoy showed more than 0.6 STI value, the wheat genotypes BARI Gom 26, BAW 1122 and BAW 1148 provided less than 0.4 STI value and the other wheat genotypes (Prodip, BARI Gom 25, BAW 1111, BAW 1118, BAW 1130, BAW 1138, BAW 1140, BAW 1142, BAW 1143, BAW 1146, BAW 1147, BAW 1150, Sonora and BAW1153) showed 0.4 to 0.6 STI value.